Effects of hazelnut husk waste on quality parameters of german primrose (Primula Obconica Hance) (Bangladesh Journal of Botany, 2023)
The study was conducted to determine the feasibility of using hazelnut shell waste as a growth medium for German primroses (Primula obconica Hance) under greenhouse conditions. Five different media combinations were prepared using sphagnum moss peat (SMP) and hazelnut husk waste (HHW). Some quality and growth parameters of P. obconica appeared to be significantly different depending on the growth medium. Results showed that HHW had a statistically significant impact on two parameters, namely aesthetic appearance score and mean flower weight, but had no impact on the other qualitative traits. The highest (8.94) and lowest (4.70) esthetic appearance scores were observed at 100% HHW and control treatments, respectively. In addition, the maximum (0.15 g) and minimum (0.097 g) mean flower weights were observed in HHW2 treatment and control plants, respectively.Bangladesh J. Bot. 52(3): 829-835, 2023 (September)